Barrier-penetrating liposome targeted delivery of basic fibroblast growth factor for spinal cord injury repair. (February 2023) - Wu, Fenzan; Wang, Penghui; Wei, Xiaojie; Yang, Yanhong; Al Mamun, Abdullah; Zhang, Xie; Zhu, Yunsen; Mo, Tingting; Zhang, Hongyu; Jiang, Chang; Hu, Jie; Xiao, Jian
Abstract: Nanoparticle technologies offer a non-invasive means to deliver basic fibroblast growth factor (bFGF) for the treatment of spinal cord injury (SCI). However, the inability of bFGF to accumulate at the injury site and inefficient penetration across the blood-spinal cord barrier (BSCB) remain challenges. The present study describes a dual-targeting liposome (bFGF@Lip-Cp&Rp) with injury lesion targeting and BSCB-penetrating capability to deliver bFGF for SCI treatment. The CAQK peptide (Cp) with injury lesion targeting ability and R2 KC peptide (Rp) with BSCB-penetrating capability were grafted onto the liposomes for a flexible and non-invasive drug delivery systems preparation. Results exhibit that the dual-targeted liposomes could significantly cross the BSCB and accumulate at the injury site. During the early stage of SCI, bFGF@Lip-Cp&Rp promotes repair of BSCB and facilitates M2-polarization of macrophages. Regular delivery of bFGF@Lip-Cp&Rp increase HUVECs tube formation and angiogenesis, ameliorate the microenvironment of lesion site, suppress the neuronal apoptosis and axonal atrophy in SCI rats. Importantly, continuous treatment of bFGF@Lip-Cp&Rp supports the restoration of limb motor function in SCI rats. In summary, this research implies that the injury site-targeting and BSCB-penetrating liposomes could be a promising therapeutic approach for the treatment of SCI. Graphical abstract: A bFGF-loaded dual-targeting liposome (bFGF@Lip-Cp&Rp) with injury lesion targeting and BSCB penetrating capability was constructed for spinal cord injury repair. Image 1 Highlights: A dual-targeted liposomes (bFGF@Lip-Cp&Rp) was prepared to deliver bFGF for SCI treatment. The bFGF@Lip-Cp&Rp shows injury lesion targeting and BSCB penetrating capability. The bFGF@Lip-Cp&Rp promotes BSCB repair, M2 macrophages polarization and angiogenesis. The bFGF@Lip-Cp&Rp promotes the recovery of motor function in SCI rats.